Assessing thermal performance: An experimental study on U-value variability in building fabric elements - H Alkhatib; P Lemarchand (Results in Engineering)
In order to achieve energy savings in existing buildings, there is an increasing need for energy audits and performance checks. In this regard, estimating a building's U-value is crucial, and there are a variety of methods available for achieving this. Heat flow meters can be used to measure U-value in situ. This research reports on an experimental campaign that evaluated the insulation and performance of the fabric elements of a building located in Dublin, Ireland. The experimental study conducted on the ''Block F'' building provided insights into the building's thermal performance by measuring the U-value of various windows and walls across different locations and floors. The average heat loss coefficient for windows was approximately 1.74 W/(m²K) before data cleaning and 1.99 W/(m²K) after cleaning, while walls had an average of 0.90 W/(m²K) before cleaning and 1.07 W/(m²K) after cleaning. The findings revealed that similar types of windows and wall components exhibited significantly different U-values. The study identified several challenges contributing to the variability in U-value readings within the same building.